Malarz śląski Johann Lichtenstein (1610 – po 1672) i jego epitafium Johanna von Götz und Schwanenfließ, prezesa rady miasta Wrocławia - Romuald Kaczmarek (Quart)
The Wrocław painter Johann Lichtenstein has been rediscovered thanks to an extensive autobiographical inscription he placed on one of his own paintings in the Church of St. Mary on the Sand in Wrocław. It tells us that he was born in Kąty Wrocławskie (German: Canth), that he left Wrocław in 1633, where he probably took his first painting lessons, and that in the course of his travels he visited the home of Peter Paul Rubens in 1636, and then, still on the move, served various mighty lords. Although he returned to Wrocław in 1648 and was active here afterwards, he did not abandon his expeditions. Unfortunately, neither of his two signed canvases in the Church of St. Mary on the Sand Wrocław survived the catastrophe of 1945. The intriguing Lichtenstein painting placed in the epitaph of a local prominent person, Johann von Götz und Schwanenfließ, president of the town council, is preserved in a terrible state in St. Elisabeth’s Church. The theme of the work is salvation, which can also be obtained by repentant sinners. This motif, depicting Biblical sinners gathered around Christ, was gaining popularity from the late 16th and early 17th c., both in Catholic (Flanders) and Protestant circles. In view of the poor state of preservation of this currently only painting by Lichtenstein, the attribution of the two portraits surviving in Wrocław to him can only be hypothetical.